Foundation of big bang cosmology reflection by a group of physicists and philosophers from the universities of Barcelona and Paris on the basic assumptions underlying sonyemporary cosmology - 390966 Seminar on Cosmological Models (1987 : University Autonoma de Barcelona)
PSZJBL